Newborn hearing loss in the south of China: a cross-sectional study - Yuanming Wang (SAGE Publishing, 2021)
Objective Newborn hearing screening can identify congenital deafness and hearing loss. The current status of newborn hearing screening in the south of China is unclear. We aimed to assess the hearing loss of newborns in Dongguan, China. Methods A total of 62,545 newborns were enrolled in this retrospective, cross-sectional study between September 2015 and August 2020. The screening procedure was carried out using a two-step hearing screening. The trends were examined by the Cochran–Armitage trend test. Results From 2015 to 2020, the total initial newborn hearing screening rate was 98.16%, and it significantly increased over time (Z = 2.488). The initial screening pass rate of newborns was 90.08%, and no significant difference was observed in the initial screening pass rate between different years (Z = 0.845). After two-step hearing screening, the overall hearing screening pass rate of newborns was 94.65%. The overall hearing screening pass rate in normal newborns was higher than that in high-risk newborns (95.70% vs. 93.59%). Conclusion The initial newborn hearing screening rate increased yearly in the study period, but there was still an approximately 10% referral rate. The initial screening pass rate in China needs to be further improved.